1998
DOI: 10.1046/j.1365-2648.1998.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Validating a measure of patient satisfaction with community nursing services

Abstract: This study describes an attempt to develop and validate a measure of patient satisfaction with a district nursing service in a south-west London inner city borough. The patients were 126 house-bound elderly people living alone and dependent upon district nursing services. The patient satisfaction measure was derived from an earlier North American questionnaire assessing satisfaction with hospital nursing services. The results indicated that the measure chosen reflected multiple dimensions of patient satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 10 publications
3
22
0
1
Order By: Relevance
“…As predicted, a positive correlation between the RCS and the Relationship VAS existed; that is, residents who rated their care providers as reliable and empathic also rated their relationships as close. The positive association between close relationships and care providers who relate well is consistent with Nussbaum's (1991) and Gilleard and Reed's (1998) findings. Nussbaum proposed that the talk within the nurse-resident interaction reveals the nature and the closeness of the relationship and suggested that researchers focus not only on the institutional level (i.e., skill mix, care models, number of personnel) when evaluating quality of care, but also on the relational level.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…As predicted, a positive correlation between the RCS and the Relationship VAS existed; that is, residents who rated their care providers as reliable and empathic also rated their relationships as close. The positive association between close relationships and care providers who relate well is consistent with Nussbaum's (1991) and Gilleard and Reed's (1998) findings. Nussbaum proposed that the talk within the nurse-resident interaction reveals the nature and the closeness of the relationship and suggested that researchers focus not only on the institutional level (i.e., skill mix, care models, number of personnel) when evaluating quality of care, but also on the relational level.…”
Section: Discussionsupporting
confidence: 82%
“…Understanding the factors, such as workload, that prevent care providers from relating well to persons during care delivery is crucial to any attempt to change the current relational care provided to residents in these environments. Relationships between increased staff-resident ratios and resident dissatisfaction with care are consistent with Gilleard and Reed's (1998) results. These investigators found that following a reduction in services, patients reported that nurses seemed busier and had less time than before.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations